Understanding early horse transport in eastern Eurasia through analysis of equine dentition. (December 2021) - Taylor, William T.T.; Cao, Jinping; Fan, Wenquan; Ma, Xiaolin; Hou, Yanfeng; Wang, Juan; Li, Yue; Zhang, Chengrui; Miton, Helena; Chechushkov, Igor; Bayarsaikhan, Jamsranjav; Cook, Robert; et al.
Abstract: Abstract : Across Eurasia, horse transport transformed ancient societies. Although evidence for chariotry is well dated, the origins of horse riding are less clear. Techniques to distinguish chariotry from riding in archaeological samples rely on elements not typically recovered from many steppe contexts. Here, the authors examine horse remains of Mongolia's Deer Stone-Khirigsuur (DSK) Complex, comparing them with ancient and modern East Asian horses used for both types of transport. DSK horses demonstrate unique dentition damage that could result from steppe chariotry, but may also indicate riding with a shallow rein angle at a fast gait. A key role for chariots in Late Bronze Age Mongolia helps explain the trajectory of horse use in early East Asia.